A novel strip-slot-strip waveguide with extremely high dispersion and large bandwidth using cascaded resonant coupling. (August 2021) - Wei, Shixiu
Highlights: A novel hybrid waveguide's proposal and its relations with its substructure. A higher dispersion with peak value −194120 ps/km-nm and bandwidth 33.6 nm at 2005 nm. How to change the bandwidth or peak value of dispersion. How to change the centre wavelength with the peak value or bandwidth unchanged. How to change the aspect ratio of this structure. Abstract: In this study, a novel strip-slot-strip hybrid waveguide was proposed for extremely high dispersion and large bandwidth. An extremely high dispersion was produced using a strong cascaded coupling effect among strip, slot, and strip waveguide modes. The properties were numerically analysed using the finite difference time-domain (FDTD) method. The results indicated that a high normal dispersion of −1.9412 × 10 5 ps/km-nm with a full width at half maximum (FWHM) of 33.6 nm around a wavelength of 2005 nm was obtained. The centre wavelength, peak value, or bandwidth of the dispersion curve could be adjusted by changing the thicknesses of the Si and Si3 N4 strips, the separation of the Si strip and slot, and the separation of the slot and Si3 N4 strip simultaneously. The two strip thicknesses, two separations, and entire structure's width could be used to change the proposed structure's aspect ratio. The performance of the proposed structure was compared to some existing structures.